Biofilm-forming properties of clinical isolates Pseudomonas aeruginosa collected from children with Cystic Fibrosis and potential Bacillus subtilis impact in vitro. - Ishchenko О. V.; Yukhymenko, A. O.; Koshova І. P.; Ilchenko S. І.; Stepanskyi D. О. (Морфологія / Morphologia / Morfologìâ, 2019)
Background. Pseudomonas aeruginosa infection determines clinical prognosis in patients with Cystic Fibrosis. Mucoid strains of P. aeruginosa are capable of forming biofilms and growing in them. Given the multiple resistance of microorganisms forming biofilms, the perspective of using Bacillus spp.for the purpose of sanitizing surfaces where pathogens may persist is being discussed. Objective. To study the biofilm-forming ability of P. aeruginosa clinical isolates from children with Cystic Fibrosis and to determine the impact of B. subtilis on them in vitro. Methods. Sputum and/or mucus samples from a deep smear from the posterior pharyngeal wall were collected from children with Cystic Fibrosis. Bacteriological, microscopic, biochemical and statistical research methods were used. The antagonistic properties of P. aeruginosa and B. subtilis were studied by the method of delayed antagonism and inco-cultivation experiments in a liquid nutrient medium followed by inoculation serial dilutions. Biofilm forming ability was determined by express-method using 96-well plates. Results. Bacteriological surveysshowed thatP. Aeruginosa was isolated from 34.21% (95% CI 32.50-35.92) of samples. It was found that B. subtilis has direct moderate antagonism againstP. aeruginosa in the delayed antagonism studyas well asafter their co-cultivation in a liquid nutrient medium.After co-cultivation the abundant growth of bacilli in all experiments at all repetitions as well as limitation of the P. aeruginosa growth was showed. The biofilm formation wasdetermined in 76.92% (95% CI 73.02-80.77) of P. aeruginosa clinical isolates, and in 100% of B. subtilis samples The B. subtilis was able to form biofilm in the presence of P. aeruginosa in most cases during co-cultivation experiments. Conclusion. Clinical isolates of P. aeruginosa isolated from children with Cystic Fibrosis are moderately susceptible to B. subtilisin vitro. Biofilm formation of P. aeruginosa can be suppressed by B. subtilis in vitro.